On large eddy simulation based conjugate heat transfer procedure for transient natural convection - Fadl, M; He, L (American Society of Mechanical Engineers, 2017)
Natural convection is an important heat transfer mode for flexible operations of gas turbines and steam turbines. Its prediction presents considerable challenges. The strong inter-dependence between fluid and solid parts points to the need for coupled fluid-solid conjugate heat transfer (CHT) methods. The fundamental fluid-solid time scale disparity is further compounded by the long-time scales of practical turbine flexible operations. In addition, if a high-fidelity flow model (e.g. Large Eddy Simulation, LES) is adopted to resolve turbulence fluctuations, extra mesh dependency on solid domain mesh may arise. In this work, understanding of the extra solid mesh dependency in a directly coupled LES based CHT procedure is gained by an interface response analysis, leading to a simple and clear characterization of erroneously predicted unsteady interface temperatures and heat fluxes. A loosely coupled unsteady CHT procedure based on a multi-scale methodology for solving problems with large time scale disparity is subsequently developed. A particular emphasis of this work is on efficient and accurate transient CHT solutions in conjunction with the turbulence eddy resolved modelling (LES) for natural convection. A two-scale flow decomposition associated with a corresponding time step split is adopted. The resultant triple-timing formation of the flow equations can be solved efficiently for the fluid-solid coupled system with disparate time scales. The problem statement, analysis and the solution methods will be presented with case studies to underline the issues of interest and to demonstrate the validity and effectiveness of the proposed methodology and implemented procedure.